2015
DOI: 10.3923/ajava.2015.690.707
|View full text |Cite
|
Sign up to set email alerts
|

Use of Maize Distiller’s Dried Grains with Solubles (DDGS) in Laying Hen Diets: Trends and Advances

Abstract: Distiller's Dried Grains with Solubles (DDGS) as untraditional feedstuff has been available for feed industry for many years and became a nutritional and economical feed ingredient. According to recent studies, DDGS is usually used at low concentrations (10 or 15%) as a feed ingredient in laying hen diets without adverse effects on laying performance, feed utilization, nutrient digestibility, egg quality criteria and economics. Because DDGS became available in feed market in large amounts, the ability of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 61 publications
1
19
0
2
Order By: Relevance
“…So, there is an urgent need for nutritious and affordable feeds. Therefore, in this study, we consider using corn distillers dried grains with solubles (DDGS) as an economic alternative source that partially replaces SBM in laying hen diets with or without exogenous enzymes to produce low‐cost formulae (Abd El‐Hack, Alagawany, Farag, & Dhama, ). Ethanol production from corn leaves a by‐product that is currently used as animal feed (Aines, Klopfenstein, & Stock, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, there is an urgent need for nutritious and affordable feeds. Therefore, in this study, we consider using corn distillers dried grains with solubles (DDGS) as an economic alternative source that partially replaces SBM in laying hen diets with or without exogenous enzymes to produce low‐cost formulae (Abd El‐Hack, Alagawany, Farag, & Dhama, ). Ethanol production from corn leaves a by‐product that is currently used as animal feed (Aines, Klopfenstein, & Stock, ).…”
Section: Introductionmentioning
confidence: 99%
“…The DDGS is a rich source of crude protein (CP), amino acids, phosphorous (P) and other nutrients in poultry diets (Abudabos, Al-Atiyat, & Khan, 2017;Świątkiewicz & Koreleski, 2008). Recently, with the increased production of biofuel, DDGS parallel increases, one of the most environmentally friend usage of DDGS in a large scale is in poultry nutrition (Abd El-Hack, El-Hindawy, Attia, & Mahrose, 2015;Abd El-Hack, Alagawany, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Distillers dried grains with solubles (DDGS) is a coproduct of corn obtained during the dry‐milling process of corn to produce ethanol after the fermentation of cornstarch by some selected yeasts. DDGS is a good source of protein, energy and amino acids for poultry (Jensen, ; Abd El‐Hack et al., ). Many researches had shown that DDGS is an acceptable ingredient in laying hen diets (Deniz et al., ; Abd El‐Hack et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Deniz et al [23] found that the inclusion of 20% DDGS significantly (P<0.05) depressed egg production of layers. More recent studies showed that rising DDGS level up to 22% decreased egg production [12,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Insoluble fibres hold water building more bulk in the animal's gut, which can reduce feed intake and subsequent production [11] . As a result of the high amount of non starch polysaccharides contetnt, mainly arabinoxylans, the optimal inclusion level of DDGS in poultry diets for maximum production is controversial [12] . The supplementation of exogenous enzymes to animal feeds in order to improve nutrient digestion is not a new idea [13,14] .…”
Section: Introductionmentioning
confidence: 99%